"Form of Life" as Transcendental Dhvani Meaning Venkataraman Prabhu (KEMANUSIAAN The Asian Journal of Humanities, 2024)
"Meaning" has been an evergreen concept in Indian philosophy and poetics. Traditional Indian philosophical and literary schools have been competing with each other in the conceptual clarification of how one arrives at the meaning of a word and on what basis. This paper is concerned with one such conception of "meaning" called dhvani (suggested meaning), aiming at a philosophical rationale for the concept of dhvani. In discourses pertaining to Indian theories of meaning, dhvani occupies an important place. Often the concept of dhvani is found in poetic and literary discourses. This paper focuses on one important aspect concerning what makes suggested meaning possible. It focuses on the philosophical rationale of how one can understand a suggested meaning. How can a suggested meaning be understood by one and not by another? What are the conditions for the possibility for an individual to understand? To answer these questions, the author follows the philosopher Wittgenstein's notion of "form of life", developing it further to claim that "form of life" is the conditions for the possibility of having a dhvani meaning. Thus this paper aims at exploring the conditions that give rise to the possibility of suggested meanings through the concept of "form of life".